A Simple and Practical Method for Rat Epididymal Sperm Count (Rattus norvegicus) - Muhammad Ja’far Luthfi (Biology, Medicine, & Natural Product Chemistry, 2015)
Sperm sample from epididymal source can be determined its number using minimal amount of equipment. These method will aid researcher and practitioner in sperm quality analysis to determined sperm number rapidly and practically.